2014
DOI: 10.1177/0269216314536947
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study investigating the effect of a patient-held pain assessment tool in palliative care outpatients attending a rural Kenyan hospital

Abstract: This study has demonstrated that a simple pain assessment tool, when linked to some action, may help achieve better analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…Other opportunities for improving care are patient education and implementation of tools that can provide patients with guidance on self-management of pain. 24 Furthermore, expanded outpatient and inpatient hospice services would improve end-of-life care for many patients. Ultimately, the economic health of Kenya will be key to improving the outlook for Kenyans with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Other opportunities for improving care are patient education and implementation of tools that can provide patients with guidance on self-management of pain. 24 Furthermore, expanded outpatient and inpatient hospice services would improve end-of-life care for many patients. Ultimately, the economic health of Kenya will be key to improving the outlook for Kenyans with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…31 Three studies excluded patients with cognitive impairment. 24,25,28 One study did not provide any patient inclusion or exclusion criteria, and all patients in the clinic were eligible for participation. 30,32 Of the 10 studies, 4 included both patients and caregivers (eg, the primary or most involved person in the patient's care), 26 patients.…”
Section: Study Country Setting Inclusion and Exclusion Criteria Samentioning
confidence: 99%
“…26,27,31 The 2 studies that included caregiver demographics of race/ethnicity also reported a predominately white sample (>70%). 27,31 The designs of the 10 studies included 2 single-group pretest-posttest, 29,32 3 quasi-experimental, 23,28,30 and 5 randomized control trials. [24][25][26][27]31 Five studies had 2 assessment points, 25,26,28,30,32 4 studies had 3 assessment points, 23,24,27,29 and 1 study had more than 3 assessment points.…”
Section: Study Country Setting Inclusion and Exclusion Criteria Samentioning
confidence: 99%
See 2 more Smart Citations